Low abundance of mitochondrial DNA changes mitochondrial status and renders cells resistant to serum starvation and sodium nitroprusside insult. (27th April 2015) - Lee, Sung Ryul; Heo, Hye Jin; Jeong, Seung Hun; Kim, Hyoung Kyu; Song, In Sung; Ko, Kyung Soo; Rhee, Byoung Doo; Kim, Nari; Han, Jin
Abstract Mutation or depletion of mitochondrial DNA (mtDNA) can cause severe mitochondrial malfunction, originating from the mitochondrion itself, or from the crosstalk between nuclei and mitochondria. However, the changes that would occur if the amount of mtDNA is diminished are less known. Thus, we generated rat myoblast H9c2 cells containing lower amounts of mtDNA via ethidium bromide and uridine supplementation. After confirming the depletion of mtDNA by quantitative PCR and gel electrophoresis analysis, we investigated the changes in mitochondrial physical parameters by using flow cytometry. We also evaluated the resistance of these cells to serum starvation and sodium nitroprusside. H9c2 cells with diminished mtDNA contents showed decreased mitochondrial membrane potential, mass, free calcium, and zinc ion contents as compared to naïve H9c2 cells. Furthermore, cytosolic and mitochondrial reactive oxygen species levels were significantly higher in mtDNA‐lowered H9c2 cells than in the naïve cells. Although the oxygen consumption rate and cell proliferation were decreased, mtDNA‐lowered H9c2 cells were more resistant to serum deprivation and nitroprusside insults than the naïve H9c2 cells. Taken together, we conclude that the low abundance of mtDNA cause changes in cellular status, such as changes in reactive oxygen species, calcium, and zinc ion levels inducing resistance to stress.